THYROTOXICOSIS WITH SEVERE HEPATIC DYSFUNCTION: A SERIES OF FOUR CASES - HC, Tee; JH, Ho; YK, Fung; KSK, Serena (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Hepatic dysfunction in thyrotoxicosis is common but rarely severe. It may be due to a multitude of reasons, namely uncontrolled thyrotoxicosis, antithyroid drugs, hepatic congestion from heart failure and associations such as autoimmune hepatitis. We report four cases with thyrotoxicosis presenting with severe hepatic dysfunction, each with a unique etiology. CASE 1 : A 33-year-old lady with type 1 diabetes mellitus and Graves’ disease presented with severe mixed cholestatichepatocellular injury without fulminant hepatic failure 3 weeks after initiating propylthiouracil (PTU). Her liver function test (LFT) improved gradually 1 week after withholding PTU. CASE 2 : A 36-year-old man with Graves’ disease presented with severe cholestatic jaundice after taking carbimazole for 1 month. Total bilirubin was markedly elevated at 426 μmol/L with mild transaminitis and normal liver ultrasound. He made a full recovery after carbimazole was discontinued. CASE 3 : A 33-year-old man presented with thyroid storm and thyrotoxic cardiomyopathy in failure. There was acute liver failure evidenced by INR of 4, total bilirubin of 173.8 μmol/L, alanine aminotransferase of 3227 U/L and aspartate aminotransferase of 3748 U/L. His LFT improved remarkably after adequate diuresis and normalization of thyroid function with Lugol’s iodine, prednisolone and cholestyramine. CASE 4 : A 53-year-old man presented with thyroid storm and jaundice with bilirubin level of 165μmol/L. Failure to improve his LFT following biochemical control with Lugol’s iodine, prednisolone and cholestyramine led to the diagnosis of autoimmune hepatitis with positive anti smooth-muscle antibody and elevated immunoglobulin G level. CONCLUSION Severe hepatic dysfunction in patients with thyrotoxicosis carries a high mortality and limits the choice of thionamide therapy because of hepatotoxicity. It is imperative to distinguish the etiology early, attain rapid biochemical control followed by early definitive therapy with radioactive iodine or thyroidectomy.